1961
DOI: 10.1002/pol.1961.1205516120
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of methacrylic anhydride with vinyl monomers

Abstract: Copolymerizations of methacrylic anhydride and a variety of common types of vinyl monomers were conducted in bulk and in solution at 60–80° with benzoyl peroxide catalyst. The copolymers were characterized by conversion, solubility in hot dimethyl sulfoxide, elementary analysis, and infrared spectroscopy. A copolymer composition equation was derived for a special divinyl–vinyl system in which the divinyl monomer would cyclize extensively during polymerization and give rise to soluble, although perhaps branched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For example, copolymerization of methacrylic anhydride with a variety of vinyl monomers has been studied. 27 It was concluded that, in general, higher conversion to soluble copolymers was realized (a) the less reactive the comonomer in radical-initiated copolymerizations, (b) the greater the dilution, (c) the greater the difference in the molar concentration of the two monomers, and (d) the lower the conversion.…”
mentioning
confidence: 99%
“…For example, copolymerization of methacrylic anhydride with a variety of vinyl monomers has been studied. 27 It was concluded that, in general, higher conversion to soluble copolymers was realized (a) the less reactive the comonomer in radical-initiated copolymerizations, (b) the greater the dilution, (c) the greater the difference in the molar concentration of the two monomers, and (d) the lower the conversion.…”
mentioning
confidence: 99%
“…In the copolymerization of monovinyl monomer (M 1 ) with divinyl monomer (M 2 ) bearing two equivalent double bonds, Eq. (1) to (4) can be given as the propagation reactions for copolymerization, when intramolecular cyclization of M 2 is not considered: On the basis of this reaction scheme, the copolymer composition equation is derived as follows: [15][16][17]…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] For example, it has been shown that the cyclopolymerization of acrylic anhydride (AA) produces both five membered and six membered rings, while MAA exclusively produces six membered rings during polymerizations conducted up to 80 °C. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] An additional and notable feature of the anhydride-containing MAA and AA diene monomers is that the anhydride moieties are able to undergo dynamic covalent exchange (DCE), which leads to the rearrangement of the polymer structure.…”
Section: Introductionmentioning
confidence: 99%